2017
DOI: 10.1088/1741-2552/aa7960
|View full text |Cite
|
Sign up to set email alerts
|

Modeling trans-spinal direct current stimulation for the modulation of the lumbar spinal motor pathways

Abstract: We provide methods and knowledge for better understanding the effects of tsDCS and serve as a basis for a more targeted and optimized application of tsDCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 53 publications
3
58
0
Order By: Relevance
“…The bottom of the anode (circular shape; 3.2 cm diameter) was placed in the midline of the vertebral column 5 cm above the upper edge of the cathode (Ugawa et al., ), corresponding to the level of the eighth thoracic spinous process (T 8 ). Based on modelling studies, this electrode configuration was chosen as it is likely to induce the greatest electric field magnitude between T 10 and T 12 spinous processes due to electric field being highest between the stimulating electrodes (Kuck et al., ). As such, the site of greatest spinal cord activation is likely to occur between the L 1 –L 5 spinal segments, corresponding to the motoneuron pools of RF and TA (Sayenko et al., ; Sharrad, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bottom of the anode (circular shape; 3.2 cm diameter) was placed in the midline of the vertebral column 5 cm above the upper edge of the cathode (Ugawa et al., ), corresponding to the level of the eighth thoracic spinous process (T 8 ). Based on modelling studies, this electrode configuration was chosen as it is likely to induce the greatest electric field magnitude between T 10 and T 12 spinous processes due to electric field being highest between the stimulating electrodes (Kuck et al., ). As such, the site of greatest spinal cord activation is likely to occur between the L 1 –L 5 spinal segments, corresponding to the motoneuron pools of RF and TA (Sayenko et al., ; Sharrad, ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on modelling studies, this electrode configuration was chosen as it is likely to induce the greatest electric field magnitude between T 10 and T 12 spinous processes due to electric field being highest between the stimulating electrodes (Kuck et al, 2017). As such, the site of greatest spinal cord activation is likely to occur between the L 1 -L 5 spinal segments, corresponding to the motoneuron pools of RF and TA (Sayenko et al, 2015;Sharrad, 1964).…”
Section: Electrical Stimulation Of the First Lumbar Spinous Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The field strength and the efficiency of tsDCS in activating the different neuronal elements in the human spinal cord therefore will strongly depend on individual differences in tissue properties and anatomical factors, as well as a range of physical factors related to the stimulation conditions (e.g., electrode size, conductive material, placement of electrodes). Studies on the distribution of the current applied by tsDCS in human participants have also indicated that the field may vary from being insufficient to reach the spinal cord at all to being sufficiently strong to influence neuronal elements in the ventral spinal cord (Bastos et al, 2016;Fernandes, Salvador, Wenger, de Carvalho, & Miranda, 2018;Kuck, Stegeman, & van Asseldonk, 2017). There is clearly a need for improved means of monitoring the distribution and strength of the applied current in individual experiments to obtain more consistent effects and in order F I G U R E 5 Effects of tsDCS on short-latency facilitation of the soleus H-reflex.…”
Section: Variability Of Effectsmentioning
confidence: 99%
“…provided mechanistic foundation to these empirical findings (29)(30)(31)(32). It is then possible that tsDCS could also influence locomotor learning.…”
Section: Introductionmentioning
confidence: 87%